Everyday Authoritarianism in North Korea. Issue 2 (7th February 2021) - Dukalskis, Alexander; Joo, Hyung-Min
Abstract: This article examines the political consequences of widespread social changes in North Korea to illuminate how, if at all, shifts in everyday life influence the power of an autocratic government. Our study is based on 23 interviews with North Korean defectors in 2017 and supplemented by interviews conducted in previous years. The main finding is that social practices associated with marketisation, flows of information, and increased corruption have not yet provided the foundation for collective challenges to the regime. It is, however, also clear that official norms, rules, and institutions have been significantly weakened to adapt to new social realities.